Leather Technology Advancements: Exploring Innovations, Applications, and Chemical Enhancements - Jaggi, Aditya Singh (Journal of Advanced Research in Glass, Leather and Plastic Technology, 2023)
This article delves into the dynamic landscape of leather technology advancements, shedding light on the latest innovations, applications, and chemical enhancements that are reshaping the timeless material. From the emergence of smart leather materials capable of adapting to environmental conditions to a heightened focus on sustainable production practices, the leather industry is undergoing a transformative phase. Biotechnological approaches, including lab-grown leathers, present cruelty-free and eco-friendly alternatives. Applications in fashion, automotive interiors, furniture, and footwear are expanding with the development of new and improved leathers, incorporating nanotechnology and eco-friendly tanning methods. The role of leather chemicals is evolving towards environmentally conscious options, influencing dyeing techniques and finishes. As the industry progresses, the collaborative efforts of science, technology, and craftsmanship are propelling leather into a future marked by innovation and sustainability.